Environmental Signals Modulate ToxT-Dependent Virulence Factor Expression in Vibrio cholerae - Schuhmacher, Darren A. (American Society for Microbiology, 1999)
The regulatory protein ToxT directly activates the transcription of virulence factors in Vibrio cholerae, including cholera toxin (CT) and the toxin-coregulated pilus (TCP). Specific environmental signals stimulate virulence factor expression by inducing the transcription of toxT. We demonstrate that transcriptional activation by the ToxT protein is also modulated by environmental signals. ToxT expressed from an inducible promoter activated high-level expression of CT and TCP in V. cholerae at 30°C, but expression of CT and TCP was significantly decreased or abolished by the addition of 0.4% bile to the medium and/or an increase of the temperature to 37°C. Also, expression of six ToxT-dependent TnphoA fusions was modulated by temperature and bile. Measurement of ToxT-dependent transcription of genes encoding CT and TCP by ctxAp- and tcpAp-luciferase fusions confirmed that negative regulation by 37°C or bile occurs at the transcriptional level in V. cholerae. Interestingly, ToxT-dependent transcription of these same promoters in Salmonella typhimurium was relatively insensitive to regulation by temperature or bile. These data are consistent with ToxT transcriptional activity being modulated by environmental signals in V. cholerae and demonstrate an additional level of complexity governing the expression of virulence factors in this pathogen. We propose that negative regulation of ToxT-dependent transcription by environmental signals prevents the incorrect temporal and spatial expression of virulence factors during cholera pathogenesis.